Whole genome sequences of 289 native cattle from Finland, the Netherlands, and Portugal - Ginja, Catarina; Gao, Junxin; Kantanen, Juha; Ghanem, Nasser; Kugonza, Donald; Makgahlela, Mahlako; Pires, Ana Elisabete; Usié, Anabel; Dibbits, Bert; de Sousa, Carolina Bruno; Gaspar, Daniel; Ruvinskiy, Daniil; et al. (Springer Nature, 2025)
Native cattle breeds in Europe are vital to agricultural heritage and livestock production, combining adaptation to diverse environments with desirable traits such as high-quality beef and milk. To investigate genetic diversity, local adaptation, and productivity-related characteristics, we generated whole-genome sequences from 289 cattle representing 11 native breeds and the commercial Holstein-Friesian breed across Finland, the Netherlands, and Portugal. These breeds span diverse climates and management systems, from cold northern regions to Mediterranean environments in southern Europe. The dataset comprises over 11 terabytes of paired-end Illumina NovaSeq6000 sequencing data, with an average depth of ~10 × and an alignment rate of ~99.7% against the ARS-UCD1.2 and 2.0 cattle reference genomes. Variant calling identified about 30 million SNPs and 2.7 million small indels distributed unevenly across the genome. Annotation linked many variants to known genes. This genomic resource provides an important foundation for studying genomic diversity, environmental adaptation, small structural variants discovery, and genomic mapping of economically important traits, offering insights for future breeding and conservation programs in European cattle.
Keywords: genome; cattle; genetic resources; sequencing